Conceptualising Multilingual Capabilities in Anglophone Higher Degree Research Education: Challenges and Possibilities for Reconfiguring Language Practices and Policies - Wei Liu (MDPI AG, 2016)
In a context of the internationalisation of Higher Education (HE) driven by the high mobility of international Higher Degree Research candidates (HDRs), it is important to consider the value of HDRs' multilingual capabilities for their learning and making of original contributions to knowledge. This article reports on a literature study regarding conceptualisations of multilingualism and multilingual capabilities, together with multilingualism in university research education practices and policies. Key themes to emerge from the literature include divergent understandings of languages, multilingualism, and multilingual capabilities. For example, a 'static' language construct provides a structuralist lens through which multilingual HDRs are viewed as an accumulation of monolinguals, whereas a 'dynamic' language construct informs a socially and culturally constructed linguistic space where the multilingual resources of HDRs are valued. These divergences are manifested in the language-as-problem orientation and language-as-resource orientation in anglophone universities' HDR education policies. Informed by empirical evidence of leveraging multilingual capabilities in original contributions to knowledge, this article argues that it is urgent for pertinent stakeholders in HDR education to reconfigure language practices and policies in the HDR educational context. In doing so, the voices of HDRs would be able to leverage multilingual capabilities in their research instead of being treated as deficient English learners.